The Risk of Downward Mobility in Educational Attainment Children of Higher-Educated Parents in Germany - Hahn, Sophie (Wiesbaden : Springer Fachmedien Wiesbaden(Imprint), 2016)
Sophie Hahn analyses downward mobility in educational attainment from a sociological life-course perspective. In order to avoid status loss children of higher-educated parents have to persevere through long educational careers. How large is their risk of intergenerational downward mobility in educational attainment and how does it shape their educational pathways? Does their parents' education still play a role in decisions at late stages of the educational career such as dropping out of and re-entering higher education? Drawing on retrospective longitudinal data of the German National Education Panel Study (NEPS) this book addresses these questions. Contents Inter- and intra-generational downward mobility in Germany Re-entering the academic pathway after starting vocational training< Access to tertiary education and dropout Target Groups Researchers and students of Sociology and Educational Science Experts, policy advisors and practitioners in education The Author Sophie Hahn is research associate at the German Youth Institute. Her research interests lie in the field of education, early childhood education and social inequality.
Inter- and intra-generational downward mobility in Germany -- Re-entering the academic pathway after starting vocational training -- Access to tertiary education and dropout.
Keywords: Sociology of Education; Social Structure, Social Inequality